PEMETAAN POTENSI SUMBER DAYA ALAM GUNA MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KECAMATAN TUKAK SADAI KABUPATEN BANGKA SELATAN - Mardiah Mardiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2015)
The potential of Tukak Sadai Sub-district has not been maximized and there is no potential mapping program in Tukak Sadai Sub-district. The location of Tukak Sadai Sub-district is in South Bangka Regency and is the smallest sub-district in size. This potential mapping is carried out by plotting the position of the location geographically using survey methods and interviews with local communities, then the results are outlined in the form of thematic maps. The results of surveys and interviews conducted obtained data in the form of information on the potential wealth of natural resources, among others: The potential of tin and its associated mineral content, agricultural and plantation potential, namely pepper, rubber and palm oil and medicinal plants, fishery potential such as kurisi fish, mackerel, shrimp, crabs and squid, tourism potential such as educational tourism about mining, underwater tourism and beach tourism.